Application of Outer Membrane Protein-Based Vaccines Against Major Bacterial Fish Pathogens in India - Maiti, Biswajit; Dubey, Saurabh; Munang'andu, Hetron Mweemba; Karunasagar, Iddya; Karunasagar, Indrani; Evensen, Øystein (Frontiers in Immunology, 2020)
Aquaculture is one of the fastest-growing food-producing sectors in the world. However, its growth is hampered by various disease problems due to infectious microorganisms, including Gram-negative bacteria in fin fish aquaculture. Disease control in aquaculture by use of antibiotics is not recommended as it leads to antibiotic residues in final the product, selection and spread of antibiotic resistance in the environment. Therefore, focus is on disease prevention by vaccination. All Gram-negative bacteria possess surface-associated outer membrane proteins (OMPs), some of which have long been recognized as potential vaccine candidates. OMPs are essential for maintaining the integrity and selective permeability of the bacterial membrane and play a key role(s) in adaptive responses of bacteria such as solute and ion uptake, iron acquisition, antimicrobial resistance, serum resistance, bile salt-resistance and some adhesins have virulence attributes. Antigenic diversity among bacterial strains even within the same bacterial species has constrained vaccine developments but OMPs that are conserved across serotypes could be used as potential candidates in vaccine development, and several studies have demonstrated their efficacy and potential as vaccine candidates. In this review, we will look into the application of OMPs for the design of vaccines based on recombinant proteins, subunit vaccines, chimeric proteins, and DNA vaccines as new generation vaccine candidates for major bacterial pathogens of fish for sustainable aquaculture.